Annealing temperature modes influence on properties of heterophase nanocomposites based on ceramics "glass - Ag-Pd" systems - Lepikh, Ya.I.; Lavrenova, T.I.; Bugayova, T.N.; Zatovskaya, N.P.; Snigur, P.O. (Functional Materials, 2014)
Temperature formation modes influence on the electric parameters and operational characteristics thick-film elements made of nanocomposite system "glass - Ag-Pd" are investigated. The manufacturing techniques are described, thick-film elements optimum modes manufacturing are determined. The developed optical attachment for thick-film element IR spectroscopy is described. The nanocomposites based on systems "glass - Ag-Pd" phase structure changing at various formation temperatures was investigated by IR-spectroscopy of reiterated total reflection method. Qualitative and quantitative chemical analyses of conducting thick-film layers are carried out. Film spectra and structure are analyzed.